Economic revival of farmwomen through broiler farming in Andaman and Nicobar Island - Nayak, Harapriya; Singh, L B; Bala, P A (Indian Farming, 2022)
A farmwoman became self-reliant and earned a decent livelihood from Broiler farming. It takes a lot of hard work and enthusiasm but it gives back much more. Her simplicity touched everyone and her efforts encouraged other farmwomen of the Island to become independent and follow her path. Several other women of the area were interested to follow her path and take up broiler farming as their main vocation and women from surrounding areas also came to her to get first-hand knowledge and suggestion regarding backyard poultry and broiler farming. In this journey of self-reliance, Smt. P Meena got full extended support in all arenas of Broiler farming and management from the ICAR-KVK, South Andaman as well as Division of Animal Science, ICAR-CIARI, Port Blair.